2018
DOI: 10.1080/2162402x.2018.1539613
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of TGF-β signaling with novel synthetic antibodies limits immune exclusion and improves chemotherapy response in metastatic ovarian cancer models

Abstract: Blockade of TGF-β signaling with novel synthetic antibodies limits immune exclusion and improves chemotherapy response in metastatic ovarian cancer models, OncoImmunology, 8:2, e1539613, ABSTRACT Epithelial ovarian cancer (EOC) is a leading cause of cancer-related death in women. EOC is often diagnosed at late stages, with peritoneal metastases and ascites production. Current surgery and platinum-based chemotherapy regimes fail to prevent recurrence in most patients. High levels of Transforming growth factor-β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…Our TGF-b pathway score was able to identify patients with different risk of platinum resistance. This is in line with previous studies showing that the TGF-b signalling participates in epithelial-mesenchymal transition (EMT) in EOC tumour cells, and in the creation of an immunosuppressive microenvironment, phenomena contributing to chemotherapy resistance [31]. Moreover, some studies have reported the involvement of TGF-b signalling in platinum resistance, both in ovarian cancer cell lines [31] and patients [32].…”
Section: Discussionsupporting
confidence: 91%
“…Our TGF-b pathway score was able to identify patients with different risk of platinum resistance. This is in line with previous studies showing that the TGF-b signalling participates in epithelial-mesenchymal transition (EMT) in EOC tumour cells, and in the creation of an immunosuppressive microenvironment, phenomena contributing to chemotherapy resistance [31]. Moreover, some studies have reported the involvement of TGF-b signalling in platinum resistance, both in ovarian cancer cell lines [31] and patients [32].…”
Section: Discussionsupporting
confidence: 91%
“…This in turn led to the development of HGS ovarian cancer precursor lesions, so-called secretory cell outgrowths (SCOUTS) and serous tubal intraepithelial carcinomas (STIC) [30]. This EMT and subsequent emergence of HGS ovarian cancer precursor lesions could be initiated by various stimuli, including TGFβ, a potent EMT-inducer present in the follicular fluid, which is released during ovulation [30,38] (Figure 1).…”
Section: Emt and High-grade Serous Ovarian Cancer Progressionmentioning
confidence: 99%
“…One example is the potent TGFβ inhibitor, SB-431542, which increased carboplatin sensitivity [61]. Likewise, synthetic inhibitory antibodies to the type II TGF-β receptor (TGFBR2), reversed EMT and improved the response to carboplatin and anti-tumor immunity in vivo (fewer Tregs and more cytotoxic immune cells in the tumors) [38]. Furthermore, treatment with siRNA targeting TWIST increased platinum sensitivity in vivo.…”
Section: Targeting Emt In Ovarian Cancermentioning
confidence: 99%
“…Newsted et al identified a lead inhibitory antigen-binding fragment (Fab) via screening of a synthetic library with TβRII. Suppression with this lead Fab resulted in the reversal of the EMT and tumor invasion and an improved response to chemotherapy in EOC xenograft and syngeneic models [115]. Genzyme (1D11) is a neutralizing monoclonal antibody active against all three isoforms of TGF-β and was shown to reduce tumor dissemination in breast cancer [116,117,118].…”
Section: Targeting Tgf-β In Ovarian Cancermentioning
confidence: 99%